Educational Development Between Faculty and Administration. (9th September 2019) - Broscheid, Andreas
Abstract: This chapter employs Identity Theory to explore the professional identities of educational developers, arguing that it is important to pay attention to the different saliences, or weights, that developers attach to the faculty and administrative sides of their identities.